A 39-year-old otherwise healthy female with acute chest pain. Issue 7 (23rd December 2015) - Mohamed Hoesein, Firdaus A A; Swaans, Martin; van Es, H Wouter
Abstract : Clinical introduction: An otherwise healthy 39-year-old female visited our emergency department because of acute chest pain worsening on breathing. The pain was more prominent on the left side of the thorax. Physical examination, routine laboratory testing and the ECG were normal. Troponin and d-dimer were in the normal range. Routine chest radiography and subsequently chest CT were performed (figure 1). Question: What is the most likely cause of the acute chest pain? Acute myocardial infarction Epipericardial fat necrosis Pneumonia Pulmonary infarction For the question see page 540 For the answer see page 547